2017
DOI: 10.3390/cli5030059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Urban Heat and Exacerbation: Development of a Heat Island Index for California

Abstract: Abstract:To further evaluate the factors influencing public heat and air-quality health, a characterization of how urban areas affect the thermal environment, particularly in terms of the air temperature, is necessary. To assist public health agencies in ranking urban areas in terms of heat stress and developing mitigation plans or allocating various resources, this study characterized urban heat in California and quantified an urban heat island index (UHII) at the census-tract level (~1 km 2 ). Multi-scale at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…The fact that cooler air can be advected away from vegetation over significant distances is important in benefiting a larger area and reducing temperaturedependent biogenic and anthropogenic emissions not only in the canopy vicinity but also in the non-vegetated surroundings (Taha 2015b). Such length scales, or "fetch", for cool-air transport are a function of wind speed (Taha et al 2018) and can be used as a basis for establishing the various heat-island mitigation modeling and implementation levels (Taha 2017).…”
Section: The Cooling Potential Of Urban Greenery Through Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that cooler air can be advected away from vegetation over significant distances is important in benefiting a larger area and reducing temperaturedependent biogenic and anthropogenic emissions not only in the canopy vicinity but also in the non-vegetated surroundings (Taha 2015b). Such length scales, or "fetch", for cool-air transport are a function of wind speed (Taha et al 2018) and can be used as a basis for establishing the various heat-island mitigation modeling and implementation levels (Taha 2017).…”
Section: The Cooling Potential Of Urban Greenery Through Ventilationmentioning
confidence: 99%
“…Some such thinking in this direction already is underway (e.g. Taha 2017;Taha et al 2018;Zhang et al 2017;Reeve et al 2015;Jim 2013;Jennings et al 2016 among others). Thus far, most studies demonstrate that there is great potential for urban greening to improve microclimate and air quality if all of the various site-specific physical and chemical processes are factored in during the design of mitigation measures.…”
Section: Greenery Emissions and Air-qualitymentioning
confidence: 99%
“…Climate change has had visible effects on many human communities all over the world, but these effects are more deeply felt in large, densely populated cities (IPCC, 2019;Bulkeley, 2013). Research has shown that urban areas are typically warmer than their rural counterparts; a difference that can be attributed to the phenomenon known as urban heat island effect (UHI) (Ward et al, 2016;Oke, 1982;Taha, 2017). This effect is strong enough to cause major physical and mental health problems for citizens (Luber & McGeehin, 2008;Tan et al, 2010;Lemonsu et al, 2015;Błażejczyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Today, heat has adversely affected urban life across the world [3], including urban areas of the Mediterranean climate [4,5]. The increase in temperature in urban areas, especially densely populated areas has given rise to the phenomenon of urban heat islands (UHI) [6,7], which can threaten the health and comfort of citizens [8,9]. The green urban spaces have been researched by numerous studies as an adaptive strategy to reduce the effect of urban heat and improve the health of citizens, by considering thermal comfort [10,11] as well as their socio-economic role [12].…”
Section: Introductionmentioning
confidence: 99%